Which explanations for gender differences in competition are consistent with a simple game theoretic model? - Christopher Cotton; Cheng Li; Frank McIntyre; Joseph Price (Queen's University, Department of Economics, 2015)
A number of recent studies show that males may increase their performance by more than females in response to competitive incentives. The literature suggests that such a male competitive advantage may contribute to observed gender gaps in labor force pay and achievement. Understanding which factors may be driving these gender differences is essential for designing policies that promote quality. Using a game theoretic model of contests, we consider a variety of explanations for the male competitive advantage that have been proposed in the empirical and experimental literature. Comparing the testable predictions of the model with the empirical evidence from past papers, we reject explanations involving male over-confidence, misperceptions about relative ability, and some types of preference differences. Explanations involving female under-confidence and differences in risk aversion are consistent with the significant evidence. Two explanations provide perfect matches to observed performance patterns: (i) males are better than females at handling competitive pressure, and (ii) males enjoy competition more or have greater desire to win than females.
Keywords: D74; J16; J24; J78; 330; contests; gender differences; competitive incentives